Analysis of Motion and Mooring of Fpso Vessels Due to Different Types of Mooring Material (Maritime Park: Journal of Maritime Technology and Society, 2024)
Mooring is a system of anchoring offshore buildings or floating models in order to survive the threat of the marine environment so that they are held in position. catenary itself is a curve-shaped structure which is usually a cable or chain that hangs freely due to its own weight with both ends held. This paper uses a numerical method based on ANSYS Hydrodynamic Diffraction to analyze the motion of the mooring rope on the FPSO with the type of mooring rope material. So as to see the differences that occur from the type of meterial used, it is necessary to analyze the mooring motion.
Keywords: Mooring, Material, Models